COVID-19 AS A POTENTIAL RISK FACTOR FOR ISCHEMIC STROKE: A CASE REPORT - Orlando Pikatan; Desie Yuliani; I Ketut Sumada; Ni Ketut Candra Wiratmi (The Indonesia Neurological Association Branch of Denpasar, 2021)
Background: Corona virus disease 2019 (COVID-19) is a pandemic disease with a wide spectrum of symptoms. Neurological symptoms are often found in this disease. Stroke on the other hand is a multifactorial disease that can be caused by a lot of underlying problems. Case: We report a case of a 67 years old man with a weakness on the right side that was worsened one day before arrival in hospital and a shortness of breath. the patient had history of stroke before, and controlled hypertension. Head Ct-scan showed a stroke infarct, and Swab RT-PCR showed + SARS-CoV-2. Discussion: Infection may become the risk factor of stroke. inflammatory mediators such as TNF-a , and CRP support the procoagulant state which leads to stroke. Conclusion: COVID-19 may increase the risk of stroke due to the inflammation state that leads to procoagulant state